2012
DOI: 10.1177/0011128712437914
|View full text |Cite
|
Sign up to set email alerts
|

To Resist or Not to Resist?

Abstract: Circumstances under which a sexual assault takes place and how these circumstances affect offenders' reactions to victim resistance are not well understood. Previous studies have not thoroughly examined the interactions that take place between situational factors and resistance. Using a combination of logistic regression and Chi-square Automatic Interaction Detection (CHAID) analyses, we examine victim, situational, and crime characteristics of 426 sexual assaults involving victim resistance to determine which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 27 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…Although Collins (2008 , pp. 174-186) considers his theory relevant for “muggings and holdups” and “armed robberies,” and despite scholarly calls for microsociological analysis of robbery violence ( Balemba, Beauregard, & Mieczkowski, 2012 ; Lindegaard, Bernasco, & Jacques, 2015 ), Collins’s theory has so far not been systematically applied to the study of robbery violence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Collins (2008 , pp. 174-186) considers his theory relevant for “muggings and holdups” and “armed robberies,” and despite scholarly calls for microsociological analysis of robbery violence ( Balemba, Beauregard, & Mieczkowski, 2012 ; Lindegaard, Bernasco, & Jacques, 2015 ), Collins’s theory has so far not been systematically applied to the study of robbery violence.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there is a need for systematic observational studies on the actual microsequences of robberies—by contrast, the offender and victim-based studies, on which Collins relies, draw conclusions from self-reported and retrospective accounts. This call for research in the actual behavioral sequence of robberies is summarized by Balemba et al (2012 , p. 607): Only after uncovering the complex offender–victim interactions that lead to varying levels of offender violence and coercion throughout the offending sequence will researchers be able to begin to advise potential victims as to the most protective course of action. …”
Section: Introductionmentioning
confidence: 99%
“…When thinking about the offense dynamic, the importance of resistance from the victim, for example, has been noted. Even though verbal and physical resistance can enable the victim to effectively avoid rape (Ullman, 2007), physical resistance has also been found to increase the chances of the aggressor becoming violent during a sexual attack (e.g., Balemba, Beauregard, & Mieczkowski, 2012). In fact, both physical and verbal resistance were found to increase lethality of a sexual assault if the perpetrator had a weapon.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of victim resistance studies have focused on the impact of that resistance on offender behavior and crime outcomes (e.g. Balemba et al, 2012; Reid and Beauregard, 2017; Tark and Kleck, 2004; Wong and Balemba, 2018). However, it is of utmost importance to adopt a victimology-centered approach to understanding victims’ behavior.…”
Section: Introductionmentioning
confidence: 99%